A Narrative Review of Dignity Therapy Research. (October 2017) - Bentley, Brenda; O'Connor, Moira; Shaw, Josephine; Breen, Lauren
Abstract : Introduction: Dignity therapy is an end‐of‐life psychological intervention that focuses on the creation of a legacy document to alleviate end‐of‐life distress. Dignity therapy is based on an empirical model of dignity at the end of life. Research on dignity therapy has been ongoing for over 12 years in 11 countries, which has created a solid empirical base. Objective: This article presents a narrative overview of the literature on dignity therapy to provide a comprehensive narrative review and critical synthesis of published research. Method: Electronic databases (PubMed, CINAHL, PsycINFO, and Scopus) were searched using the key terms "dignity therapy, " "dignity psychotherapy, " and "Chochinov" from 2000 to March 2016. Results: Thirty‐nine publications were included and findings were grouped into the following areas: Efficacy; Feasibility with different study populations; Web‐assisted delivery; Impact on families; Cultural studies; Case studies; Themes found in documents; Clinical perspectives; and Implementation studies. Conclusions: While dignity therapy is well accepted in most cases, it may not always be effective, therapeutically valid, or practical, and may cause family or cultural frictions. It is recommended that clinicians take into consideration each person's unique circumstances in relation to the current literature before undertaking dignity therapy. Future research is indicated to evaluate dignity therapy with different cultural groups, to investigate the views of recipients of dignity therapy documents, to discover the time and resource commitments required to deliver dignity therapy, to identify who should provide dignity therapy, and to examine the experiences of clinicians who deliver dignity therapy. More research is also needed comparing dignity therapy to other end‐of‐life interventions.